Solar irradiation in diffusely enclosures with partitions - Miguel, A. F. (2012)
In this paper, we investigate the performance of indoor partitions arranged in different geometries on the income of solar irradiation within hemi-cylindrical enclosures partially transparent to solar radiation. The importance of the geometry and of the optical properties of the partition in blocking the admission of solar irradiation is indicated.